ЗАБЕЗПЕЧЕННЯ ГНУЧКОСТІ СИСТЕМИ ГОСПОДАРЮВАННЯ ЗАЛІЗОРУДНОГО ПІДПРИЄМСТВА ЗА УМОВ НЕСТАБІЛЬНОСТІ ПАРАМЕТРІВ ЙОГО РИНКОВОГО ПРОСТОРУ (International Journal of Innovative Technologies in Economy, 2019)
In crisis conditions of entrepreneurial activity and in the conditions of instability of the market environment, the issue of providing flexibility to the iron and steel enterprises management system becomes of paramount importance in order to optimize their production programs and maximize profitability. The article generates a generalized sequence of phases of the life cycle of iron ore production for specific periods of its operation in certain sectors of the market space. The phases of the life cycle of iron ore products are planned, which are planned to be implemented on priority and, to some extent, unpredictable sectors of the market space.The conceptual provisions of the system of monitoring the situation in the strategic zones of management of the iron ore enterprise have been developed, which allows solving the cardinal issues related to long-term forecasting taking into account adjustment of strategic goals and ways of their achievement in the field of modernization, technical re-equipment, reconstruction, reengineering, reorganization, reforming, restructuring of the iron ore enterprise.